2021
DOI: 10.1097/nor.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Ability to Recognize and Prevent Opioid-Induced Respiratory Depression

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Another intervention research, developed in an orthopedic adult unit, in a 660-bed teaching hospital in a metropolitan area of the Midwest of Minneapolis revealed that nurses strongly evaluated the POSS scale as an appropriate instrument for patients receiving opioids in the acute postoperative period. The test had a high result in nursing confidence and regarding the information with which to make clinical decisions (κ = 0.909) (14) . Contributions carried out by specialists improved the items and allowed the creation of understandable sentences without prejudicing the equivalence between versions.…”
Section: Discussionmentioning
confidence: 99%
“…Another intervention research, developed in an orthopedic adult unit, in a 660-bed teaching hospital in a metropolitan area of the Midwest of Minneapolis revealed that nurses strongly evaluated the POSS scale as an appropriate instrument for patients receiving opioids in the acute postoperative period. The test had a high result in nursing confidence and regarding the information with which to make clinical decisions (κ = 0.909) (14) . Contributions carried out by specialists improved the items and allowed the creation of understandable sentences without prejudicing the equivalence between versions.…”
Section: Discussionmentioning
confidence: 99%
“…Em outra pesquisa de intervenção desenvolvida em unidade adulta ortopédica, em hospital de ensino de 660 leitos em uma área metropolitana no meio-oeste de Minneapolis, revelou que os enfermeiros avaliaram fortemente que a escala POSS é um instrumento apropriado para pacientes recebendo opioides em pós-operatório agudo, pontuando mais alto em confiança da enfermagem e informações fornecidas sobre as quais fazer decisões clínicas (κ = 0,909) (14) .…”
Section: Discussionunclassified
“…To provide safe pain management, organizations must ensure patients are monitored for side effects and adverse outcomes, such as opioid-induced respiratory depression (OIRD) which is a potentially lethal, but preventable, adverse outcome related to opioid consumption. To prevent OIRD and consequential dangerous sequelae, it is critical that organizations prioritize patient safety, educate all clinicians to intervene, and maintain evidence-informed policies that include assessments and interventions to recognize and treat OIRD (ECRI Institute, 2017; Jungquist et al, 2020; McNaughton et al, 2021).…”
Section: Barriers and Challenges To Providing Effective Pain Managementmentioning
confidence: 99%